2021
DOI: 10.1126/scitranslmed.abe2587
|View full text |Cite
|
Sign up to set email alerts
|

SHP2 drives inflammation-triggered insulin resistance by reshaping tissue macrophage populations

Abstract: Insulin resistance is a key event in type 2 diabetes onset and a major comorbidity of obesity. It results from a combination of fat excess–triggered defects, including lipotoxicity and metaflammation, but the causal mechanisms remain difficult to identify. Here, we report that hyperactivation of the tyrosine phosphatase SHP2 found in Noonan syndrome (NS) led to an unsuspected insulin resistance profile uncoupled from altered lipid management (for example, obesity or ectopic lipid deposits) in both patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 59 publications
0
17
1
Order By: Relevance
“…By contrast, depletion of macrophages or pharmacological inhibition of SHP2 improved insulin sensitivity and reduced metaflammation. 84 Choi et al similarly showed that insulin stimulation triggered a negative feedback pathway involving SHP2-MAPK that phosphorylated the insulin receptor substrate 1/2 and then promoted endocytosis, which inhibited the insulin receptor-mediated activation of PI3K-AKT signaling. 85 SHP099, an allosteric inhibitor of SHP2, blocked this feedback regulation, prolonged insulin action on metabolism, and improved insulin sensitivity in a high-fat-diet-induced mouse model of diabetes.…”
Section: The Signaling Pathways Regulated By the Protein Phosphatases...mentioning
confidence: 99%
“…By contrast, depletion of macrophages or pharmacological inhibition of SHP2 improved insulin sensitivity and reduced metaflammation. 84 Choi et al similarly showed that insulin stimulation triggered a negative feedback pathway involving SHP2-MAPK that phosphorylated the insulin receptor substrate 1/2 and then promoted endocytosis, which inhibited the insulin receptor-mediated activation of PI3K-AKT signaling. 85 SHP099, an allosteric inhibitor of SHP2, blocked this feedback regulation, prolonged insulin action on metabolism, and improved insulin sensitivity in a high-fat-diet-induced mouse model of diabetes.…”
Section: The Signaling Pathways Regulated By the Protein Phosphatases...mentioning
confidence: 99%
“…SHP2 is closely associated with the immune response, cancer development, cellular metabolism, and cell growth 33,34 . Additionally, SHP2 has been shown to promote a proinflammatory phenotype of macrophages, modify resident macrophage homeostasis, and trigger monocyte infiltration 35 . Thus, higher expression of SHP2 might regulate the function of macrophages in H. pylori ‐associated gastritis tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme targets include cGAS ( Ablasser and Chen, 2019 ); the kinases JAK1/2 ( Hoang et al., 2021 ), ephrin-B3 ( Clark et al., 2021 ), and Fgr ( Crainiciuc et al., 2022 ); the tyrosine phosphatase SHP2 ( Paccoud et al., 2021 ); the proteases proprotein convertase subtilisin/Kexin 9 (PCSK 9) ( Patriki et al., 2022 ) and the immunoproteasome ( Ah Kioon et al., 2021 ; Kirk et al., 2021 ); the 8-oxoguanine DNA glycosylase OGG-1 ( Visnes et al., 2018 ); and the histone 3 Lys27 trimethyltransferase Ezh2 ( Zhang et al., 2018 ). Adaptor protein targets include STING ( Ablasser and Chen, 2019 ) and NRLP3 ( Wang et al., 2022 ).…”
Section: Suppressing Inflammationmentioning
confidence: 99%